2020
DOI: 10.1055/s-0040-1709704
|View full text |Cite
|
Sign up to set email alerts
|

Glutaric Aciduria Type 1: A Case Report and Review of Literature

Abstract: An 8-month-old male infant patient was referred to our institution (from elsewhere) with a history of fever, convulsions, dystonic posturing, altered sensorium, and loss of motor and mental milestones since past 1 month. Upon admission to our institution, a neuroimaging (magnetic resonance imaging of the brain) revealed frontoparietal atrophy, “bat-wing appearance,” and basal ganglia changes. Carnitine and acylcarnitine profile revealed low total carnitine, very low free carnitine, and low free/acylcarnitine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The distribution of the clinical and biochemical phenotypes was similar in all groups and no differences in outcome were noted amongst these variants. Researchers have tried for years to find a link between the genotype and phenotype of these patients in an effort to predict their prognosis with limited success ( Sanju et al, 2021 ; Sitta et al, 2021 ). Recently, an Egyptian study suggested that six variants: p.Trp50Arg, p.Glu64Asp, p.Ser119Leu, p.Arg128Gln, p.Ser139Leu, and p.Arg402Trp, might present with a genotype-phenotype correlation, indicating a poor outcome ( Mosaeilhy et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the clinical and biochemical phenotypes was similar in all groups and no differences in outcome were noted amongst these variants. Researchers have tried for years to find a link between the genotype and phenotype of these patients in an effort to predict their prognosis with limited success ( Sanju et al, 2021 ; Sitta et al, 2021 ). Recently, an Egyptian study suggested that six variants: p.Trp50Arg, p.Glu64Asp, p.Ser119Leu, p.Arg128Gln, p.Ser139Leu, and p.Arg402Trp, might present with a genotype-phenotype correlation, indicating a poor outcome ( Mosaeilhy et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…neurodevelopmental impairment, epilepsy, dementia, tremor) and psychiatric (e.g. BPD, anxiety) symptoms (da Costa Ferreira et al, 2008;Goodman et al, 1998;Pokora et al, 2019;Ramsay et al, 2018;Sanju et al, 2020).…”
Section: Prevalence Of Treatable Genetic Disorder Variants Within the Study Cohortmentioning
confidence: 99%
“…Affected patients may develop normally up to 1-2 years of age; macrocephaly is a common finding and precedes the onset of neurological manifestations. If untreated, 90% of patients between 3 and 36 months of age suffer regression and severe dystonic-dyskinetic disorder [3 , 4] . Cognitive functions are relatively spared [4] .…”
Section: Introductionmentioning
confidence: 99%